Caryophyllaceae endémicas del Perú - Cano, Asunción (2006)
The Caryophyllaceae are represented in Peru by 19 genera and 126 species (Brako & Zarucchi, 1993), mainly herbs and subshrubs. Here we recognize 44 endemic taxa in 11 genera. We applied IUCN categories and criteria to 43 taxa. Endemic taxa are found mainly in the High- Andean and Mesoandean regions, between 2500 and 4950 m elevation. Ten endemic species have been registered within Peru´s protected areas system.